Identifikasi Objek Wisata Potensial dan Strategi Pengelolaan dalam Mendukung Pendapatan Asli Daerah Pemerintah Kota Kupang - Charles Kapioru (Jurnal Inovasi Kebijakan, 2019)
This research was conducted to determine tourism objects in The City of Kupang, as well as conservation strategies and the development of the area into a tourist destination. The research method used was a survey method, and field observations. The number of samples taken consisted of 2 people, each from the Arts and Culture Tourism Office, and Tourism Business Managers, in addition, the other 6 samples are the community, which was determined intentionally (purposive sampling), while 10 other samples were randomly appointed (accidental sampling), i.e. tourists, who are visiting the tourism area. Research findings: First, the tourism object consists of cultural heritage, museums, art works, churches, mosques, all natural with beautiful architects, ecotourism objects (protected forests, mangrove forests, beaches, natural caves, natural springs, agro-tourism areas) and other attractions, such as special interest tourism objects. The contribution of the tourism sector to Regional Original Revenues in 2018 amounted to 15.95%, with an average annual growth of 31%. Second, the strategic steps for the development of tourism areas are budget allocation for the development of tourism potential, including ecotourism objects, enhancing the quality of The Apparatus to overcome tourism problems, minimizing environmental damage as a result of developing tourism areas, increasing tourism promotion through online media, mass media, brochures and leaflets; and increasing the level of community participation, starting from the planning up to the implementation stage of tourism development. Thus, the Government must be more proactive in promoting tourism and building synergies with communities around tourism objects.